Efecto de tres dosis de Humus de Lombriz y un comparador de Nitrogeno en el rendimiento del cultivo de Caihua (cyclanthera pedata) en el distrito de la Banda de Shilcayo - Gonzáles Hidalgo, John Albert (2011)
The present qualified work of investigation (research) " Effect of three doses of humus of worm and a comparator of N in the performance(yield) of the culture(culturing) of caihua (Cyclanthera pedata L.) in the Band of Shilcayo ", was realized by the intention of evaluating three doses of humus of worm and a comparator of N. in the performance(yield) of the culture(culturing) of caihua (Cyclanthera pedata) where there were used three doses of humus of worm (T3 = 2.0 kg ha-1, T4 = 4.0 kg ha-1, T5 = 6.0 Kg ha-1), A mineral dose urea (68,83 Kg ha-1) and an absolute witness (without security). There being evaluated the number of branches, size of fruits in cm, number of fruits / plants, weight in Kg / fruit, weight in kg / hectare., and economic Analysis. The best results being obtained for the treatment T2 (68.83 Kg ha-1 of N) by 13.00 branches / plants, 16.10 cm of length / fruit, by an average of 13.65 fruits / plant(floor), a weight of 0.064 Kg / fruit, managing to obtain a performance(yield) (1820.800 Kg ha-1), achieving a benefit costo/ of 55.46 %. Likewise the T5 (6 Kg ha-1) with 16,25 branches / plants, 17.00 cm of length / fruit, with an average of 14.37 fruits / plant(floor), a weight of 0.059 Kg / fruit, managing to obtain a performance(yield) (1511.900 Kg ha-1), with a benefit cost of 0.17 % Fits to mention that the effect of the humus of worm like organic amendment turns out to be the most favorable, for improving the conditions of the soil and producing raw material(commodity) with metabolites organic. Key Words: worm Humus, performance, organic amendment